PENGARUH PENERAPAN KNOWLADGE MANAGEMENT DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PT CPJF FRAM 1 PADANG PARIAMAN - Riri Mayliza; Asra Tanjung (LP2M Universitas Bina Bangsa, 2022)
This type of research is quantitative which is research which emphasize on cognitive assay – theory passes through research variable with numeral and does analisis data with statistical procedure. This research slated to test implement influences knowladge management and human resource development for performance to fire an employee PT CPJF Fram 1 Pariaman's Moorland. With samples taking tech total population be made by sample by totals sample as much 67 employees PT CPJF Fram 1 Pariaman's Moorlands. Analisis is data utilizes to program SPSS. This observational result is Yielding hypthosts testing first be gotten knowledge management having for for performance to fire an employee. That probe this variable have influence that signifikan at indication with degree signifikansi is smaller of 0,05 which is 0,000. Hypthosts testing result both of acquired that human resource development having for for performance to fire an employee. This was seen from smaller signifikansi degree of 0,05 which is 0,002